Effect of Tillage Method and Mulch Application on Growth and Yield of Green Gram in Semiarid Kenya - Robert O. Hakim; Josiah. M. Kinama; Onesmus M. Kitonyo; George N Chemining’wa (Advances in Agriculture)
Conservation tillage is regarded as the best practice for crop production in drylands. However, their effect on the green gram (Vigna radiata (L) Wilczek) has not been much documented in ASALs of Kenya. A field study was conducted during the 2018-2019 short rains with the aim of evaluating the effect of tillage methods and mulch application on the growth and yield of two green gram varieties in Katumani and Mwea. A randomized complete block design (RCBD) with a split-slit plot arrangement and three replicates was used. The main plots were tillage methods zero tillage (ZT), furrow-ridge (FR), and conventional tillage (CT). Subplots were mulched plots with plant residue (3 t·ha−1) and plots without mulch applied (0 t·ha−1) and in the sub-subplots were two green gram varieties (N26 and KS20). Data was collected on plant height, number of primary branches, root biomass, shoot biomass, number of pods per plant, number of seeds per pod, 1000 seed weight, grain weight (t·ha1), and harvest index. Data was subjected to the general analysis of variance using GenStat 15th statistical software. Mean separation was calculated using the least significant difference LSD at a 5% probability level. Results showed that tillage methods and mulch application significantly affected growth, yield, and yield component. Furrow-ridge recorded superior effects ahead of zero tillage and conventional tillage. Mulch application had significant effects on growth, yield, and yield component. Variety N26 under the treatment of furrow-ridge mulched with 3 t·ha−1 had a greater number of branches, plant height, yield, and yield components in both experiment sites. The application of mulch had a positive impact on growth, yield, and yield component. Furrow-ridge and zero tillage with mulch emerged to be the most efficient techniques for better green gram yield in Katumani and Mwea. This can be recommended for increased crop production in areas that receive insufficient rainfall.